Advances in the treatment of multiple sclerosis through monoclonal antibody Ocrelizumab - Silva, Jonatas Gonçalves da; Pezzini, Marina Ferri; Poeta, Julia (Medicina (Ribeirao Preto), 2020)
Objective: Evaluating the effectiveness and risks associated with the treatment of multiple sclerosis with the monoclonal antibody Ocrelizumab.Methods: The study consists of a narrative review that aimed to search articles evidencing the effects of the Ocrelizumab drug for the recurrent and primary progressive forms of multiple sclerosis. The search was carried out in PubMed, BVS, Cochrane Library, and ScienceDirect databases from 2011. The articles were pre-selected through the title and abstract for full reading and included or excluded in the study according to predetermined criteria.Results: A total of 743 articles were retrieved, 23 of which were considered eligible for comprehensive analysis and 20 were excluded because they did not fit into the outcomes proposed. Three studies were included. All studies have demonstrated the high efficacy of Ocrelizumab free of opportunistic infections.Conclusion: Despite the degenerative nature of MS, technological advances in therapy through drugs such as Ocrelizumab bring promising results, such as reduced annual outbreak rates, the number of MRI injuries, and the progress of the disability. However, due to its recent approval, it is not possible to evaluate the long-term effects of monoclonal antibody use.